Reactive-loaded antenna designs for ultra-wideband (UWB) applications
Ultra wideband (UWB) technology have attracted incredible research attention from research institution and industry due to its exclusive characteristics. The need of UWB antenna is speedily growth for many types of UWB applications. The challenges on designing UWB antenna are to produce the required operating bandwidth, an adequate gain with stable radiation pattern, and compact size of antenna. In this thesis, the research study is focused on the antenna design, development, and prototyping the UWB antennas for UWB application that fulfil the characteristics. Reactively loading technique is chosen as the method to provide those appealing characteristics. This technique includes slots, notches, and slits. The selected technique has features that can provide UWB antenna with requires operating bandwidth, compactness, stable radiation pattern, and acceptable gain. Five UWB antennas have been designed, fabricated and their performances are investigated comprehensively. The first antenna is designed on FR4 substrate which comprises of unsymmetrical rectangular radiating element with slots, and symmetrical slots with slit on the ground plane. The second antenna has multi-slots circular radiating element, a partial ground plane, and a ground plane on top with slits that is fabricated on FR4 substrate. The design of third antenna has multi-slots in the radiating element, slot in the feed line, conductor-backed planes under the FR4 substrate, and two partial ground planes. The fourth antenna consists of slot in the radiating element, multi-slots on the ground plane, a conductor-backed plane under the substrate and slits on the ground plane on top. The fourth antenna is fabricated on the FR4 substrate. The fifth antenna is designed with same configuration as the fourth antenna but using a different substrate which is Taconic (TLY-5A). The UWB antennas have been fabricated and measured in an anechoic chamber in order to observe their performances. From observation, all antennas achieved fractional bandwidth more than 100 % that covered the entire UWB operating bandwidth from 3.1 GHz to 10.6 GHz, exhibit stable nearly omni-directional radiation pattern and appropriate maximum gain of 7.35 dBi. These behaviours prove that those antennas have high potential for being used in UWB applications includes radar, imaging, sensor, communication, and others. Based on this research, the second antenna achieved a very wideband operating bandwidth up to 32 GHz. Therefore, the second antenna can be applied for future application such as SG application and others.